Predictors of cigarette and water pipe smoking behaviours among female school students aged 12-19 years in Jeddah, Saudi Arabia - Alotaibi, Amani Awwadh (2016)
Water pipe smoking is an increasing public health concern, with supportive global reports of higher prevalence than cigarette among female school students particularly in the Middle East countries. The objective of this study was to determine the prevalence and predictors of cigarette and water pipe smoking behaviours among female school students (aged 12-19 years) in Jeddah, Saudi Arabia. A cross-sectional study was carried out among Saudi female school students aged 12 to 19 years in Jeddah. A multistage probability proportionate to size sampling method was applied. Sample size (N=5,150) was calculated using a formula for testing hypothesis of two population proportions. The data was collected using validated selfadministrated questionnaire that requiring information on smoking behaviours, as well as selected demographic, social, attitudinal/ environmental and psychological variables. Data was analysed using SPSS version 21. Pearson’s chi-square test was used to determine the differences in the prevalence of smoking and factors. Multivariate logistic regression was used for determining predictors of smoking behaviours. The prevalence of ever water pipe smoking was 36.2% while cigarette smoking prevalence was 30.9%. The prevalence of current water pipe smoking was about double that of cigarette smoking (15.8% and 9.1% respectively). Bivariate analysis showed that smoking prevalence was significantly (P<0.05) higher among private school students than public school students, for current cigarette smoking (35.3% and 28.3% respectively) and for ever water pipe smoking (41.1% and 35.2% respectively). The multivariate analysis showed that, close friend’s smoking, number of smoking friends, accessibility to smoking and self-efficacy to resist smoking were significant predictors for both ever and current cigarette/ water pipe smoking behaviours among the respondents. Among the predictors, close friend’s smoking was the strongest predictor for ever cigarette smoking (AOR=1.73, 95%CI:1.39-2.15), while sister’s smoking was the strongest predictor for ever water pipe smoking (AOR=3.24, 95%CI:2.47-4.25) among the respondents. Father’s smoking, brother’s smoking and perceived difficulty to quit smoking were significant predictors of respondents’ ever cigarette and water pipe smoking, but not with current smoking behaviours. Exposure to second hand smoking in homes was significant predictor of current cigarette smoking (AOR=1.42, 95%CI:1.04-1.93) while exposure to second hand smoking in public places was predictor of current water pipe smoking (AOR=1.47, 95%CI:1.12- 1.92). Student allowance and exposure to pro-smoking messages in stores were significantly predicted cigarette smoking behaviour while parents’ educational levels, family structure, perceived prevalence of smoking, perceived parents’ disapproval of smoking, exposure to smoking control activities, depression and stress were significant predictors of respondents’ water pipe smoking behaviour. In conclusion, ever water pipe smoking (36.2%) and cigarette smoking behaiours (30.9%) are highly prevalent among Saudi female school students in Jeddah. The findings of the predictors highlighted the need for development and enhancement of more effective anti-smoking intervention programs for the female school students in Jeddah to help them change their positive normative perceptions and attitudes towards smoking and to improve their smoking refusal skills.